Social Capital and Human Mortality: Explaining the Rural Paradox with County-Level Mortality Data - Yang, Tse-Chuan (Rural Sociol, 2011)
The “rural paradox” refers to standardized mortality rates in rural areas that are unexpectedly low in view of well-known economic and infrastructural disadvantages there. We explore this paradox by incorporating social capital, a promising explanatory factor that has seldom been incorporated into residential mortality research. We do so while being attentive to spatial dependence, a statistical problem often ignored in mortality research. Analyzing data for counties in the contiguous United States, we find that: (1) the rural paradox is confirmed with both metro/non-metro and rural-urban continuum codes, (2) social capital significantly reduces the impacts of residence on mortality after controlling for race/ethnicity and socioeconomic covariates, (3) this attenuation is greater when a spatial perspective is imposed on the analysis, (4) social capital is negatively associated with mortality at the county level, and (5) spatial dependence is strongly in evidence. A spatial approach is necessary in county-level analyses such as ours to yield unbiased estimates and optimal model fit.